Digital crowdsourcing and public understandings of the past: citizen historians meet Criminal Characters. Issue 3 (2nd July 2020) - Piper, Alana
Abstract: Criminal Characters is a research project examining both who criminals actually were, and who they were imagined to be, in order to deconstruct historical and contemporary understandings of 'the criminal' as a form of social identity. In particular, it aims to deepen public and academic understandings of the characteristics of historical offenders by using crowdsourcing to transcribe the detailed biographic and criminal career information held in Victoria's prison registers from the 1850s to 1940s. This article will use Criminal Characters as a case study for discussing the challenges and opportunities presented by engaging public volunteers to perform research tasks. It will question the degree to which the terms 'crowdsourcing' and 'citizen science' can be considered interchangeable, and how digital history projects can be designed to incorporate crowdsourcing in ways that facilitate volunteers becoming 'citizen historians' who gain greater historical literacy as a result of their contributions. The benefits of such collaborative processes and knowledge exchange for criminal justice history will be explored.